(3WQb NUNUI GdeQGab GdYGeI (B:s (3GdGeJjGR (B-(3GdTQcGJ GdeNJdWI (B-BOT-(3JahjV GdeQab GdYGe (B/s - (3GdbWH, eQhGf eMj GdOjfs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3jVe eaghe GdeQab GdYGe GdEbJUGOj GdUfGYj hGdJLGQj, GdWQb GdJbdjOjI dNUNUI GdeQGab GdYGeI, GdWQb GdeYGUQI dNUNUI GdeQGab GdYGeI, JahjV GdeQab GdYGes
(3HjHdjhZQGajG(B: (3U U(B.527-538s
Keywords: (3GdbWGY GdNGUs; (3GdbWGY GdYGes; (3GdeQGab GdYGeIs